Green roof and louvers shading for sustainable mosque buildings in Riyadh, Saudi Arabia - Alabdullatief, Aasem; Omer, Siddig; Elabdein, Rami Zein; Alfraidi, Sultan (2016)
The number of mosque buildings is continuously increasing with the Muslim population, which is in fast growth around the world. In particular, the demand of new mosque buildings is high in the urban areas, due to increasing urban population growth in many parts of Muslims countries, as a result of economic growth and political instabilities in some parts of the Muslims world. Mosques are becoming more overcrowded and as a result a number of researches have been conducted to address the issue of thermal comfort of mosque users. Additionally, mosque building is unique because of its intermittent operation and various users, which require a unique heating or cooling strategies. On the other hand due to environmental pressure to suppress global warming, more energy efficient and sustainable buildings design is one of the current issues in building industries. This research aims to explore the sustainable techniques for mosque buildings in different climate zones. This research assesses a number of mosques buildings in different parts of the world with different climate; and investigates the strategies employed to cool or heat these buildings depending on the climate and season. The effectiveness of the building features in relation to each climate are carefully analysed, and possibility of potential replication of these features elsewhere are examined. This paper examined two techniques, green roof and louver shading in hot arid climate. The eventual objectives are establishing a guideline for architects and mosques building designer at any climate in order to achieve sustainable mosque building. The study concludes that there is a potential saving of up to 10% in cooling loads when green roof and louvers shading are applied on simulated mosque building in Riyadh, thus achieving the environmental feasibility in addition to economic and social benefits.